2012
DOI: 10.1113/jphysiol.2012.241786
|View full text |Cite
|
Sign up to set email alerts
|

Direct and GABA‐mediated indirect effects of nicotinic ACh receptor agonists on striatal neurones

Abstract: Key points• Pharmacological activation of nicotinic ACh receptors (nAChRs) excites striatal interneurones and induces a GABA-mediated current in medium spiny projecting neurones (MSNs) via feedforward inhibition. Abstract Choline acetyltransferase-expressing interneurones (ChAT)+ of the striatum influence the activity of medium spiny projecting neurones (MSNs) and striatal output via a disynaptic mechanism that involves GABAergic neurotransmission. Using transgenic mice that allow visual identification of MSN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
90
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(99 citation statements)
references
References 50 publications
7
90
2
Order By: Relevance
“…This nicotinic receptor profile differs from that striatal FSIs and NPY-NGF GABAergic interneurons (Koós and Tepper, 2002, English et al, 2012) but is consistent with a recent report by Luo and colleagues (2013) that found the same antagonist sensitivities for striatal Type I THINs as we report here, and additionally demonstrated that striatal Type I THINs respond to cytisine, a selective α3β4 agonist nicotinic agonist. Here we show additionally that although all THINs tested exhibited a nicotinic excitation with a similar or identical pharmacology, there appeared to be subtype-specific differences in the strength of the excitation.…”
Section: Discussionsupporting
confidence: 93%
“…This nicotinic receptor profile differs from that striatal FSIs and NPY-NGF GABAergic interneurons (Koós and Tepper, 2002, English et al, 2012) but is consistent with a recent report by Luo and colleagues (2013) that found the same antagonist sensitivities for striatal Type I THINs as we report here, and additionally demonstrated that striatal Type I THINs respond to cytisine, a selective α3β4 agonist nicotinic agonist. Here we show additionally that although all THINs tested exhibited a nicotinic excitation with a similar or identical pharmacology, there appeared to be subtype-specific differences in the strength of the excitation.…”
Section: Discussionsupporting
confidence: 93%
“…3 and 7). Although NPY-NGF interneurons are sparsely distributed in the striatum, considering the reported high-connectivity to SPNs (∼60-87%) (26,55), single NPY-NGF interneurons might possess more powerful inhibition to the striatal network than we expected.…”
Section: Discussioncontrasting
confidence: 39%
“…Therefore, dendritic plateau potentials could be sustained despite FS-mediated inhibition. Another interesting finding is the very effective inhibition mediated by GABAergic IPSCs with slow kinetics, presumably mediated by NPY-NGF interneurons (26,55). Dendritic slow GABAergic IPSCs showed the strongest efficacy in dendritic inhibition (Figs.…”
Section: Discussionmentioning
confidence: 98%
“…Vicini's (Ade et al 2008;Janssen et al 2009;Janssen et al 2011;Luo et al 2013) and other groups (Kirmse et al 2008;Janssen et al 2009;Santhakumar et al 2010) have provided solid evidence for the presence and the developmental profile of a tonic GABA A current in MSNs. (Note, however, that one study did not find any evidence for a tonic GABA A current in D2 + or D1 + MSNs; Gertler et al 2008.)…”
Section: Striatummentioning
confidence: 98%